THE RATIONAL TRAIN SPEED CHOICE PROBLEM WITH THE HELP OF MATHEMATICAL MODELING OF THE RAILWAY SECTION EXPLOITATION PROCESS - Kharlan, V. I.; Kurhan, D. M.; Bondarenko, I. O. (Science and Transport Progress, 2007)
The method of an establishment of rational speeds of movement in view of change of a condition of objects in time by means of modeling process of operation of a railway as set of objects by use of functions of set is offered.